The Impact of Using Quick Response (QR) Codes on Improving Learning and Retention of Science among Sixth-Grade Female Students in District 19 of Tehran - Moghimi Firozabad, Masoumeh; Hashemi, Zahra Sadat; Samadi, Saba (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The purpose of this study is to examine the impact of this technology in the field of education, particularly in the domain of science education. Methods and Materials: This research falls under the category of quantitative studies and is quasi-experimental in nature, using a control group and an experimental group with a pre-test and post-test design. The statistical population of the study consists of all sixth-grade female students in District 19 of Tehran who are studying in the 2022-2023 academic year. A total of 70 students were selected as a sample using convenience sampling. To control and assess the level of learning and retention in the subjects, a test was designed by the researcher on the relevant topic. The content and face validity of the researcher-designed tests were confirmed by five sixth-grade teachers and instructors of in-service courses for sixth-grade science. After checking the assumptions, a covariance test was conducted to verify the research hypotheses. Findings: The results showed that at the 0.05 level, the means of the two groups had a significant difference. Conclusion: This means that the use of QR codes, in conjunction with teacher instruction, had a positive and significant impact on the students' learning and retention scores.